2004
DOI: 10.1063/1.1767597
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ge nanocrystals in HfAlO high-k dielectric and application in memory device

Abstract: Formation of Ge nanocrystals embedded in HfAlO high-k dielectric by co-sputtering of HfO2, Al2O3, and Ge, followed by rapid thermal annealing was demonstrated. Analysis by transmission electron microscopy and x-ray photoelectron spectroscopy confirmed the formation of nonoxidized Ge nanocrystals with a minimum size of about 5nm embedded in HfAlO dielectric. We also demonstrated the application of such nanocrystals in nonvolatile memory devices, achieving a 2.2V memory window as obtained from the C–V characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 6 publications
0
38
0
1
Order By: Relevance
“…Embedded nanoparticles also show interesting physical phenomenon as compared to the isolated nanoparticles or bulk materials [7] and find new applications in electronics devices [8][9][10]. Germanium nanoparticles in silica glass matrix was found to show super heating during melting and super cooling during crystallization which lead to hysteresis of the melting temperature as high as 17% [7].…”
Section: Introductionmentioning
confidence: 97%
“…Embedded nanoparticles also show interesting physical phenomenon as compared to the isolated nanoparticles or bulk materials [7] and find new applications in electronics devices [8][9][10]. Germanium nanoparticles in silica glass matrix was found to show super heating during melting and super cooling during crystallization which lead to hysteresis of the melting temperature as high as 17% [7].…”
Section: Introductionmentioning
confidence: 97%
“…However, a few studies have reported on Ge nanocrystals embedded in other matrix materials such as Al 2 O 3 , 1 SiC, 2 AlN, 3 and HfAlO. 4 Because the surfaces and interfaces of nanoscale materials can play a dominant role in determining their properties, it is interesting to compare the properties of nanocrystals embedded in different matrices. For example, though quantum mechanical models predict efficient size-dependent photoluminescence from group IV semiconductor nanocrystals, the reported luminescence from silica-embedded Ge nanocrystals has mostly been attributed to defects within the oxide or at the oxide/nanocrystal interface.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It is also expected that Al addition will enlarge the band gap of HfO 2 . 8 Although numerous papers have appeared in the past two years addressing the physical/electrical properties of hafnium aluminate as a gate dielectric, [9][10][11][12] the basic microstructure and electronic structure of these amorphous materials remain unclear.…”
Section: Introductionmentioning
confidence: 99%